Seven women : and the secret of their greatness - Metaxas, Eric (Nashville, Tennessee : Nelson Books, an imprint of Thomas Nelson, 2015)
Offers seven captivating portraits of some of history's greatest women, each of whom changed the course of history by following God's calling.
Joan of Arc -- Susanna Wesley -- Hannah More -- Saint Maria of Paris -- Corrie ten Boom -- Rosa Parks -- Mother Teresa.
Includes bibliographical references (pages 193-205) and index.
Keywords: Christian women -- Biography; Christian women -- Religious life